Creative collaboration: architects and artists-decorators in the public buildings of the 1930 and 1940 - Duran, Cecilia (Universidad Nacional de Mar del Plata. Facultad de Arquitectura, Urbanismo y Diseño, 2018)
The article examines the collaboration between architects and visual artists that took place in the context of the construction of a series of public buildings during the 1930s and early 1940s in Argentina. We look into the aesthetic and ideological debates which underlay this modernizing trend of public architecture that found in the appeal to a renewed decoration (murals, stained glass windows, reliefs and sculptures) the keys to redefine the communicative capacity of the discipline in a moment in which modernization processes threatened to eliminate it. Several discussions are analized, some on the place of art in modern architecture, others on the role of public art in the embellishment of the city, its potential as a pedagogical instrument and at the same time as a means of political propaganda. The study of this trend shows that the aesthetic dimension of architecture had a fundamental role for this trend of architectural modernism, whose specific contribution has not been sufficiently valued by specialized historiography. We consider that such central importance was associated with the public nature of the artistic and architectural objects that were used by state and civil society institutions to communicate political ideas and spread social imaginaries through them.